Using artificial intelligence to improve healthcare delivery in select allied health disciplines: a scoping review protocol - Kristina Edvardsson; Sally Fowler-Davis; Claire Thwaites; Ken Ho; Kalpana Raghunathan; Meg E. Morris; Tafheem A. Wani; Casey Peiris; Jonathan P. McKercher; Sharon Bourke; Saadia Danish; Jacqueline Johnston; et al. (BMJ Open)
Introduction Methods to adopt artificial intelligence (AI) in healthcare clinical practice remain unclear. The potential for rapid integration of AI-enabled technologies across healthcare settings coupled with the growing digital divide in the health sector highlights the need to examine AI use by health professionals, especially in allied health disciplines with emerging AI use such as physiotherapy, occupational therapy, speech pathology, podiatry and dietetics. This protocol details the methodology for a scoping review on the use of AI-enabled technology in sectors of the allied health workforce. The research question is ‘How is AI used by sectors of the allied health workforce to improve patient safety, quality of care and outcomes, and what is the quality of evidence supporting this use?’Methods and analysis The review will follow the Joanna Briggs Institute scoping review guidelines. Databases will be searched from 17 to 24 March 2025 and will include PubMed/Medline, Embase, PsycINFO and Cummulative Index to Nursing and Allied Health Literature databases. Dual screening against inclusion criteria will be applied for study selection. Peer-reviewed articles reporting primary research in allied healthcare published in English within the last 10 years will be included. Studies will be evaluated using the Quality Assessment with Diverse Studies tool. The review will map the existing literature and identify key themes related to the use of AI in the disciplines of physiotherapy, occupational therapy, speech pathology, podiatry and dietetics.Ethics and dissemination No ethics approval will be sought, as only secondary research outputs will be used. Findings will be disseminated through peer-reviewed publication and presentations at workshops and conferences.Trial registration number Open Science Framework Protocol Registration https://osf.io/r7t4s